Effects of Culture on Firm Risk-Taking : A Cross-Country and Cross-Industry Analysis - Mihet, Roxana (Washington, D.C. : International Monetary Fund, 2012)
This paper investigates the effects of national culture on firm risk-taking, using a comprehensive dataset covering 50,000 firms in 400 industries in 51 countries. Risk-taking is found to be higher for domestic firms in countries with low uncertainty aversion, low tolerance for hierarchical relationships, and high individualism. Domestic firms in such countries tend to take substantially more risk in industries which are more informationally opaque (e.g. finance, mining, IT). Risk-taking by foreign firms is best explained by the cultural norms of their country of origin. These cultural norms do not proxy for legal constraints, insurance safety nets, or economic development.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet